DANA TRANSFER DAN BELANJA MODAL PADA KABUPATEN DAN KOTA DI PROVINSI ACEH - Arrahman, Berryl Chaliq; Jalaluddin, Jalaluddin (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2024)
This study examines the effect of special autonomy funds, general allocation funds, and revenue-sharing funds on capital expenditure of districts/cities in Aceh Province. The population in this study was 23 districts/cities of the Aceh Regional Government. The sampling technique used purposive sampling. The data type used is secondary data obtained directly from the budget realization report. This study uses multiple linear regression analysis methods with the help of IBM SPSS Statistics 23 software. The research findings show that special autonomy funds and revenue-sharing funds affect capital expenditure, while general allocation funds do not affect capital expenditure. Special autonomy funds, general allocation funds, and revenue-sharing funds simultaneously affect regional spending.